2015
DOI: 10.1039/c5nr02384j
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte multilayer-assisted fabrication of non-periodic silicon nanocolumn substrates for cellular interface applications

Abstract: Recent advances in nanostructure-based biotechnology have resulted in a growing demand for vertical nanostructure substrates with elaborate control over the nanoscale geometry and a high-throughput preparation. In this work, we report the fabrication of non-periodic vertical silicon nanocolumn substrates via polyelectrolyte multilayer-enabled randomized nanosphere lithography. Owing to layer-by-layer deposited polyelectrolyte adhesives, uniformly-separated polystyrene nanospheres were securely attached on larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 47 publications
(79 reference statements)
0
28
0
Order By: Relevance
“…Diverse types of cells adhere and proliferate (C.-H. Choi et al 2007; Nomura et al 2005; Hu et al 2010) on pillar substrates and spread on high aspect ratio vertical nanostructures while maintaining their physiological activity (S. Lee et al2015).…”
Section: Interaction Mechanisms Of Cells and Vertical Structures At Dmentioning
confidence: 99%
“…Diverse types of cells adhere and proliferate (C.-H. Choi et al 2007; Nomura et al 2005; Hu et al 2010) on pillar substrates and spread on high aspect ratio vertical nanostructures while maintaining their physiological activity (S. Lee et al2015).…”
Section: Interaction Mechanisms Of Cells and Vertical Structures At Dmentioning
confidence: 99%
“…Recent studies have used micro- and nanometer-scale engineered structures to mimic extracellular matrices and other biological structures, which have led to a groundbreaking understanding of the physical cues and molecular signal transduction pathways for integrin activated focal adhesion, protein adsorption, and pseudopodia formation [1,2,3,4,5,6,7,8,9]. Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [1,3,4,5,7,8,10,11,12,13,14,15,16,17,18,19,20]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that cellular responses often depend on the mechanical properties, pattern structures, and surface chemistry of the microenvironment surrounding the cells [1,3,4,5,7,8,10,11,12,13,14,15,16,17,18,19,20]; however, work done thus far has been conducted with structures composed of monolithic materials having uniform surface chemical composition. Studies of cell behavior on nanocomposite surfaces are limited [1,3,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanisms that drive cell behavior on engineered surfaces, researchers often visually inspect cell surface morphology. However, it could be argued that some of the most important information in determining cell behavior is located on the underbelly of the cell, where the cell meets the substrate [10,18,19]. Are cells that have been observed to float on top of dense pillar patterns [10,18,19,20] or narrowly spaced line structures [21] truly floating?…”
Section: Introductionmentioning
confidence: 99%
“…However, it could be argued that some of the most important information in determining cell behavior is located on the underbelly of the cell, where the cell meets the substrate [10,18,19]. Are cells that have been observed to float on top of dense pillar patterns [10,18,19,20] or narrowly spaced line structures [21] truly floating? It is known that on widely spaced topographic features, cells wrap around the features [1,13,20,22] thus maximizing their contact.…”
Section: Introductionmentioning
confidence: 99%